Manejo integrado de residuos sólidos enfocados al desarrollo local de la parroquia Poaló, 2021 - Viera Muñoz, José Francisco (2022)
The objective of this project is to design a comprehensive solid waste management system oriented to the local development of the San José de Poaló Parish. As a result of a poor recycling culture, indeterminate waste collection hours and insufficient garbage containers, the environment and people's health are affected. To achieve the goals, five main points were identified for the classification of all solid waste. Data were collected at each point over seven days to determine the kilograms of waste per day obtained. The methodology focused on the qualitative analysis applied in a direct observation and an interview. In addition, quantitative disaggregation was used through the statistical analysis of a survey and weighing of solid waste. The average weight per day obtained in the five points studied was 3,935 kg per day, with paper being the highest type of waste with 0.731 kg per day, followed by cardboard with 0.689 kg per day and food waste and shrubs pruned with 0.616 kg per day. Once the results were compared and analyzed, an environmental management program was designed where we have 5 proposals such as: impact prevention and mitigation program, community relations program, solid waste collection and transportation program, environmental education training program, and solid organic waste management (only recyclable). Likewise, a SWOT matrix was made with the bases for the creation of a community company that will be in charge of buying and selling recycled material to the people of the community or even the province. The prompt implementation of the integrated solid waste management system will make it possible to adequately attend to local waste.